The revival of the Flâneur : analysing narratives of Flânerie in W. G. Sebald‟s Austerlitz and Teju Cole‟s Open City. - Rowshon, Sabah Tasnia (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2019.